2019
DOI: 10.1177/0954410019855576
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual-level evaluation of a variable stiffness skin for a morphing wing leading edge

Abstract: A morphing leading edge produces a continuous aerodynamic surface that has no gaps between the moving and fixed parts. The continuous seamless shape has the potential to reduce drag, compared to conventional devices, such as slats that produce a discrete aerofoil shape change. However, the morphing leading edge has to achieve the required target shape by deforming from the baseline shape under the aerodynamic loads. In this paper, a conceptual-level method is proposed to evaluate the morphing leading edge stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A possible solution for such a system in a morphing CFRP structure is described in [6]. Further improvement of aerodynamic performance for morphing systems may be achieved using an integrated aerodynamic optimisation approach, which considers material limitations like the one reported in [43] together with structural optimisation algorithms, e.g., [44].…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution for such a system in a morphing CFRP structure is described in [6]. Further improvement of aerodynamic performance for morphing systems may be achieved using an integrated aerodynamic optimisation approach, which considers material limitations like the one reported in [43] together with structural optimisation algorithms, e.g., [44].…”
Section: Discussionmentioning
confidence: 99%
“…8 Related researches have indicated that the airfoil performance can be further improved by optimizing the leading edge portion. [9][10][11] Therefore, this paper devotes to optimize the LE geometry and reveal the flow mechanism for further improving the aerodynamic performance of this new type VIGV.…”
Section: Introductionmentioning
confidence: 99%
“…In other projects investigating morphing droop noses, a droop nose with flexible skin and kinematics was designed, manufactured and tested, with fiber optic distributed shape sensing via Rayleigh backscattering used to reconstruct the deployed shapes [20]. A conceptual numerical study on a variable stiffness skin by means of continuously variable ply angles as opposed to variable-thickness-laminates is presented in [21]. Wind tunnel tests of a flexible wing leading edge with compliant mechanisms are presented in [22,23] and additional compliant mechanism designs are presented in [24].…”
Section: Introductionmentioning
confidence: 99%